The Influence of Social Support on Physical Activity in Chinese Adolescents: The Mediating Role of Exercise Self-Efficacy - Zhanbing Ren; Linlin Hu; Jane Jie Yu; Qian Yu; Sitong Chen; Yudan Ma; Jingyuan Lin; Lin Yang; Xiaoyun Li; Liye Zou (MDPI AG, 2020)
The purpose of this study was to examine the associations of social support and self-efficacy with physical Activity (PA) and the mediating effect of self-efficacy on the relationship between social support and PA in Chinese adolescents. Participants included a total of 2341 Chinese adolescents (aged 12.75 ± 1.46 years). Self-reported instruments, including the physical activity questionnaire for adolescents, the social support revalued scale and the exercise self-efficacy scale, were used to measure physical activity, social support and exercise self-efficacy. Results showed that social support (r = 0.29, p < 0.05) and exercise self-efficacy (r = 0.43, p < 0.05) were significant and positive predictors of PA among Chinese adolescents, and exercise self-efficacy was a significant mediator in the relationship between social support and PA (standardized effect size = 0.15, p < 0.001). Such findings were evident with similar patterns in both male and female adolescents. The findings of this study have indicated the importance of social support and exercise self-efficacy on PA promotion in adolescents, which will aid the development of effective interventions in this population.